Turning the lab into Jeremy Bentham's panopticon: The effect of punishment on offenders and non-offenders - Christoph Engel; Bernd Irlenbusch (Max Planck Institute for Research on Collective Goods, 2010)
The most famous element in Bentham's theory of punishment, the Panopticon Prison, expresses his view of the two purposes of punishment, deterrence and special prevention. We investigate Bentham's intuition in a public goods lab experiment by manipulating how much information on punishment experienced by others is available to would-be offenders. Compared with the tone that Jeremy Bentham set, our results are non-expected: If would-be offenders learn about contributions and punishment of others at the individual level, they contribute much less to the public project. Our results confirm the special prevention effect but show that the deterrence effect is smaller the more information on individual punishment is available.
Keywords: C91; H41; K14; K42; 330; Punishment; Deterrence; Special Prevention; Jeremy Bentham; Experiment; Public Good; Strafe; Kriminalpolitik; Informationsverbreitung; Öffentliches Gut; Trittbrettfahrerverhalten; Test